The Effect of Experience Quality, Customer Perceived Value and Customer Satisfaction on Customer Loyalty of Outdoor Restaurant During the Covid-19 Pandemic - Wuisan, Dewi; Elton, Kenny (ADI Publisher, 2021)
The purpose of this study was to determine customer loyalty from using experience quality, customer perceived value and customer satisfaction variables. Cork & Screw Restaurant, located in Jakarta a restaurant outdoor concept restaurant so how customer loyalty is at this restaurant especially during the Covid 19 pandemic, outdoor concept restaurants are the customer's choice. In this study, using variables are experience quality, customer perceived value and customer satisfaction, and variable customer loyalty. The population in this study is for consumers who have visited and eaten at the Cork & Schew restaurant. Sample size using 260 respondents, sampling technique is Non Probability Sampling with purposive sampling method, data collection techniques with electronic and online questionnaries (G-form), measurement Scale: Interval scale with Likert scale and data Analysis Method: Structural Equation Modeling – Partial Least Square 3.0 Program. The results of this study indicate that experience quality has a positive effect on customer perceived value, customer satisfaction and customer loyalty. In the customer variable, perceived value shows a positive effect on customer satisfaction and customer loyalty.